Analysis of the voltage profile in transmission lines operating with injected third harmonic voltages - Santos Ferrari, Júlio Cesar [UNESP]; Justo de Araújo, Anderson Ricardo; Kurokawa, Sérgio [UNESP] (Elsevier, 2021)
This paper analyses the voltage profile along a three-phase transmission line whose power transfer capability was increased by an uprating technique based on the injection of a third harmonic voltage component. The superposition of a third harmonic voltage component with the fundamental component at the sending and receiving ends of the line proposes to increase the amplitude of the fundamental voltage component without exceeding the electrical insulation voltage limits, and thus increasing the power transfer capability. However, this uprating technique can affect the voltage amplitudes significantly along the line. In some cases, these amplitudes can be higher than acceptable values. The study was carried out in Simulink/MatLab® software. Two three-phase uprated transmission lines with voltages of 230 kV and 735 kV were represented by the Bergeron's line model, then voltage profiles and the voltage waveforms in the time domain at the midpoint of each simulated system were obtained. Results have shown that 230-kV transmission lines with lengths of up to 300 km operating under natural to heavy load conditions can be uprated by the THV technique, whereas 735-kV transmission lines have presented overvoltages along its length when operating between light and natural loading, attesting that this technique is not feasible for this system.
Keywords: Power capability; Third harmonic voltage; Transmission lines; Uprating technique